ANALISIS YURIDIS TERHADAP KERUSAKAN KAWASAN RESAPAN AIR DI BATURRADEN KABUPATEN BANYUMAS AKIBAT AKTIVITAS PARIWISATA DAN PEMBANGUNAN - Carmo Carmo; Eti Mul Erowati Erowati; Wiwin Muchtar Wiyono; Elly Kristiani Purwendah (Ganesha Law Review, 2026)
This study provides a juridical analysis of the damage to the water catchment area in Baturraden, Banyumas Regency, caused by tourism activities and development. Water catchment areas play a strategic role in maintaining hydrological balance, particularly in regulating water systems, preventing floods, and preserving groundwater availability. However, the increasing tourism activities and infrastructure development in the area may lead to environmental degradation, which disrupts the ecological function of the water catchment area. This research employs a normative juridical method using statutory and conceptual approaches to examine legal regulations concerning the protection of water catchment areas. The findings indicate that the legal framework governing water catchment protection has been regulated under various legal instruments; however, its implementation still faces challenges in terms of supervision, law enforcement, and consistency in spatial planning policies. Therefore, strengthening legal instruments and optimizing the role of local governments are necessary to ensure the sustainability of the water catchment function in Baturraden.